Copper oxide nanoparticles inhibit pancreatic tumor growth primarily by targeting tumor initiating cells - Benguigui, Madeleine; Weitz, Iris S.; Timaner, Michael; Kan, Tal; Shechter, Dvir; Perlman, Or; Sivan, Sarit; Raviv, Ziv; Azhari, Haim; Shaked, Yuval (Scientific reports, 2019)
Cancer stem cells, also termed tumor initiating cells (TICs), are a rare population of cells within the tumor mass which initiate tumor growth and metastasis. In pancreatic cancer, TICs significantly contribute to tumor re-growth after therapy, due to their intrinsic resistance. Here we demonstrate that copper oxide nanoparticles (CuO-NPs) are cytotoxic against TIC-enriched PANC1 human pancreatic cancer cell cultures. Specifically, treatment with CuO-NPs decreases cell viability and increases apoptosis in TIC-enriched PANC1 cultures to a greater extent than in standard PANC1 cultures. These effects are associated with increased reactive oxygen species (ROS) levels, and reduced mitochondrial membrane potential. Furthermore, we demonstrate that CuO-NPs inhibit tumor growth in a pancreatic tumor model in mice. Tumors from mice treated with CuO-NPs contain a significantly higher number of apoptotic TICs in comparison to tumors from untreated mice, confirming that CuO-NPs target TICs in vivo . Overall, our findings highlight the potential of using CuO-NPs as a new therapeutic modality for pancreatic cancer.